Cognitive impact in children with “benign” childhood focal epilepsy with centrotemporal spikes (Archives of Clinical Psychiatry, 2017)
Background Cognitive alterations are associated with benign childhood focal epilepsy with centrotemporal spikes (BCECTS) including aspects of executive functions. Objectives This study presents the performance profile on attention and executive function tests of fifty-eight children (BCECTS, n = 30 and controls, n = 28) aged 8-13 years. Methods The following tools were employed: Vocabulary and Block Design subtests from the Wechsler Intelligence Scale for Children III, Stroop Test, Modified Card Sorting Test, Controlled Oral Word Association – FAS and Tower of London. Results Children with BCECTS presented average IQ measure, although their performance was statistically worse when compared to the control group. Children with BCECTS showed significantly lower performance compared to the control group in the following variables: total number of recollected words on the oral fluency test, total number of categories, categorization effect and total number of errors in MCST; and execution time for the Stroop Test Card 1. After controlling for the IQ effect, the total number of errors in the MCST did not show any significant difference between the groups. Discussion Children with BCECTS showed lower performance in attention and executive functions when compared to healthy children. The results suggest that the concept of “benign” BCECTS should be reconsidered.